Middle meningeal artery embolization without surgical evacuation for chronic subdural hematoma: a single-center experience of 209 cases - Orscelik, Atakan; Senol, Yigit Can; Bilgin, Cem; Kobeissi, Hassan; Arul, Santhosh; Cloft, Harry; Lanzino, Giuseppe; Kallmes, David F.; Brinjikji, Waleed (Frontiers in Neurology, 2023)
Background Middle meningeal artery (MMA) embolization is a minimally invasive treatment option for new and recurrent chronic subdural hematomas (cSDH). Objective To examine the safety and efficacy profile of MMA embolization without surgical evacuation for cSDH patients. Methods A single-center retrospective study of patients with cSDHs treated by MMA embolization was undertaken. Patient demographics, hematoma characteristics, procedural details, and clinical and radiological outcomes were collected. The primary outcome was the need for retreatment, and the secondary outcomes were at least a 50% reduction in the maximum width of cSDH on the last CT imaging, complications, and an improvement in the modified Rankin scale (mRS) score. All results were presented as descriptive statistics. Results A total of 209 MMA embolizations were successfully performed on 144 patients. Polyvinyl alcohol particles were the primary embolization agent in all procedures. Of the total of 206 cSDH, the median maximum width at pre-intervention and last follow-up were 12 and 3 mm, respectively, and the median reduction percentage was 77.5%, with a >50% improvement observed in 72.8% at the last follow-up imaging. A total of 13.8% of patients needed retreatment for recurrent, refractory, or symptomatic hematomas after embolization. The mRS score improved in 71 (49.3%) patients. Of 144 patients, 4 (2.8%) experienced complications related to the procedure, and 12 (8.4%) died during follow-up due to causes unrelated to the MMA embolization procedures. Conclusion This study supports the fact that MMA embolization without surgical evacuation is a safe and effective minimally invasive option for the treatment of cSDHs.